Spin reorientation transition driven by polaronic states in Nd2CuO4. Issue 20 (12th August 2022) - Banik, Soma; Vijay, Kritika; Paul, Suvankar; Mansuri, Najnin; Shukla, D. K.; Srivastava, S. K.; Sagdeo, Archna; Kumar, Kranti; Tripathi, Shilpa; Jha, S. N.
Abstract : We show that the spin reorientation transitions in Nd2 CuO4 are associated with the polaronic states and depend on the electronic interactions between the bulk and the surface. Abstract : We show that the spin reorientation transition in Nd2 CuO4 is due to the electronic interactions between the bulk and the surface. Electron-like doping due to the small oxygen deficiency in Nd2 CuO4 gives rise to the localized Nd 2+ states on the surface while the bulk has dominating Nd 3+ states. Nd 2+ states act like bound polaronic in-gap states on the surface, which are hybridized with the Cu–O charge transfer band. Polaron–polaron interactions lead to ferromagnetic correlations and also decrease the energy gap across the spin reorientation transition. Drastic variation in the density of states along with valence band narrowing at low temperature indicates the bulk–surface interaction between the Nd 3+ and Nd 2+ states through the Cu–O spin cloud. Short range electron–lattice interaction due to the bound polaronic states with large negative Seebeck coefficient (−535 μV K −1 at 300 K) suggests electron doped Nd2 CuO4 as a potential thermoelectric material.